Dynamic risk management: Theory and evidence - FEHLE, F; TSYPLAKOV, S (Journal of Financial Economics, 2005)
We present and test an infinite-horizon, continuous-time model of a firm that can dynamically adjust the use of risk management instruments which seek to reduce product price uncertainty and thereby mitigate financial distress losses and reduce taxes. The dynamic setting relaxes several restrictive assumptions common to static models. In the model, the firm can adjust its use and the hedge ratio and maturity of risk management instruments over time, risk management instruments expire as time progresses, the available maturity of the risk management instruments is shorter than the lifetime of the firm, and transaction costs are associated with initiation and adjustment of risk management contracts. The model produces a number of new time-series and cross-sectional implications on how firms use short-term instruments to hedge long-term cash flow uncertainty. Numerical results describe the optimal timing, adjustment, and rollover of risk management instruments and the choice of contract maturity and hedge ratio in response to changes in the firm's product price. The results show that the structure of transaction costs can have an important effect on the firm's risk management strategy. The model predicts that firms that are either far from financial distress or deep in financial distress neither initiate nor adjust their risk management instruments, while firms between the two extremes initiate and actively adjust their risk management instruments. Using quarterly panel data on gold mining firms between 1993 and 1999, we find evidence of a non-monotonic relation between measures of financial distress and risk management activity consistent with the model. We also provide evidence supportive of the model's predictions with respect to the maturity choice of risk management contracts.